Global Structuring of Phylogenetic and Functional Diversity of Pelagic Fungi by Depth and Temperature - Morales, Sergio E.; Biswas, Ambarish; Herndl, Gerhard J.; Baltar, Federico (Frontiers in Marine Science, 2019)
Fungal contributions to ecosystem processes are well documented for terrestrial systems yet oceans, which account for most of the Earth’s surface, have remained poorly explored with regards to organisms in this kingdom. Here, we demonstrate that, although in low relative abundance (i.e,. fungal reads made up 1.4-2.9% of the metagenomes), fungi contribute to both phylogenetic and functional microbial diversity with a conserved fungal presence in global marine samples. Universally distributed taxa and functions implicate them in complex carbon and fatty acid metabolism, with depth stratification along pelagic zones. Functional differences in observed genes between epipelagic and mesopelagic waters indicate changes in UV protection, shift to carbohydrate limited diets, as well as alternative energy sources. Metagenomic data also provided evidence for a latitudinal gradient in fungal diversity linked to temperature shifts. Our results suggest that fungi contribute to multiple biogeochemical cycles in the pelagic ocean, and could be integral for ecosystem functioning through provision of key nutrients.